Embryonic stem cells and the challenge of transplantation tolerance. - Fairchild, P; Cartland, S; Nolan, K; Waldmann, H (2004)
Isolated from early blastocysts, embryonic stem (ES) cells capture the brief moment of pluripotency in the developing embryo, as evidenced by their differentiation into many somatic cell types in vitro. Although these properties might help meet the growing demand for 'spare parts' to replace diseased or worn-out tissues, their use in so-called cell replacement therapy (CRT) poses several challenges, not least of which is the prevention of their subsequent rejection. Here we explore the notion that ES cells might spawn cell types necessary for the treatment of disease while acting as a plentiful source of hematopoietic stem cells (HSCs) or terminally differentiated dendritic cells (DCs) that might facilitate the induction of transplantation tolerance to the replacement tissues.